Gaya Kepemimpinan, Insentif Dan Lingkungan Kerja Terhadap Prestasi Kerja Pegawai Pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Bogor - Dora, Lika (Jurnal Manajemen, 2018)
This study aims to examine and analyze the Influence of Leadership Style, Incentives and Work Environment on Job Performance in Department of Public Works and Spatial Planning of Bogor Regency. Data collection was done by distributing questionnaires and implemented for 118 employees. Data analysis in this research using SPSS version 24. The results of this study explain that between leadership style, incentive and work environment have a significant influence on the performance of employees partially and simultaneously. For the variable that has the most dominant influence on the work performance is the style of leadership, so to obtain optimal employee performance hence leadership style factors, incentives and work environment needs to be improved.